Integrating Diagnostic and Therapeutic Expertise: A Review of Laboratory–Pharmacy Collaboration in Optimizing Medical Treatment - Talbi, Jaber Hamoud Ali; Albaqami, Nawaf Jazaa; Alsulami, Metab Ahmad; Alharbi, Yousuf Saleem; Alqarni, Ali Saeed Saad; Thagafi, Bassim Saleh Awed Al (Journal of Posthumanism, 2024)
The increasing complexity of modern healthcare has intensified the need for effective integration between diagnostic and therapeutic services. Collaboration between laboratory and pharmacy professionals represents a critical yet underutilized strategy for optimizing medical treatment, enhancing patient safety, and improving clinical outcomes. This review examines the scope, mechanisms, and impact of laboratory–pharmacy collaboration across diverse healthcare settings. It synthesizes evidence on how coordinated use of laboratory data—such as biomarkers, culture results, and organ function indicators—supports accurate medication selection, dosing optimization, therapeutic drug monitoring, and early detection of adverse drug reactions. The review further explores collaborative roles in antimicrobial stewardship, chronic disease management, critical care, and precision medicine. In addition to clinical benefits, system-level outcomes including workflow efficiency, cost-effectiveness, and quality performance are discussed. Emerging digital solutions, including electronic health records, clinical decision support systems, and artificial intelligence–enabled analytics, are highlighted as enablers of diagnostic–therapeutic integration. Barriers to effective collaboration, such as professional silos and technological limitations, are also examined. Overall, this review underscores that structured laboratory–pharmacy collaboration is a key component of high-quality, patient-centered care and a strategic priority for healthcare systems seeking to optimize medical treatment.